1997
DOI: 10.1093/jnci/89.11.766
|View full text |Cite
|
Sign up to set email alerts
|

Breast Cancer: Weighing the Evidence for a Promoting Role of Dietary Fat

Abstract: It has been hypothesized that a high-fat diet promotes the development of postmenopausal breast cancer. This contention is supported by data showing high international correlations between fat intake and breast cancer rates, modest positive associations with a high-fat diet in case-control studies, and animal model studies that have consistently demonstrated that dietary fat influences mammary cancer development at several stages in the carcinogenic process. A number of plausible biologic mechanisms have been … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
69
0
7

Year Published

1999
1999
2013
2013

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 153 publications
(78 citation statements)
references
References 128 publications
2
69
0
7
Order By: Relevance
“…In chemically induced mammary tumor animal models, highfat diets are associated with increased tumor incidence, and this effect is diminished by antioxidants (vitamin E and selenium), observations that would support a role for lipid peroxidation (18,19). However, Horvath and Ip (19) reported that, although supplementation of the diet with two antioxidants, vitamin E and selenium, inhibited 7,12-dimethylbenz(a)anthracene tumor development, the indices of lipid peroxidation did not decrease in parallel with tumor incidence in this model (20). The systemic suppression of lipid peroxidation by vitamin E alone was not sufficient to inhibit mammary tumor formation.…”
Section: Evaluation Of the Experimental Evidence In Breast Carcinogenmentioning
confidence: 94%
“…In chemically induced mammary tumor animal models, highfat diets are associated with increased tumor incidence, and this effect is diminished by antioxidants (vitamin E and selenium), observations that would support a role for lipid peroxidation (18,19). However, Horvath and Ip (19) reported that, although supplementation of the diet with two antioxidants, vitamin E and selenium, inhibited 7,12-dimethylbenz(a)anthracene tumor development, the indices of lipid peroxidation did not decrease in parallel with tumor incidence in this model (20). The systemic suppression of lipid peroxidation by vitamin E alone was not sufficient to inhibit mammary tumor formation.…”
Section: Evaluation Of the Experimental Evidence In Breast Carcinogenmentioning
confidence: 94%
“…A current view is that the mammary tumorigenic-enhancing activities of a high-fat diet is, at least in part, through a caloric mechanism [Welsch, 1994]. Epidemiologic investigations regarding the relationship between the amount and the type of fat consumed and breast cancer have produced conflicting results [Hunter et al, 1996;Clavel-Chapelon et al, 1997;Wynder et al, 1997;Woutersen et al, 1999] and a mechanism by which dietary fat may modulate carcinogenesis has not been elucidated.…”
Section: A Role For Dietary Fat In the Epidemiology Of Breast Cancermentioning
confidence: 99%
“…It has been suggested that lifestyle factors and dietary habits may modulate the indices of breast cancer progression (Wynder et al, 1963;Gregorio et al, 1985;Holm et al, 1989). Dietary interventions currently under study for their possible effects on breast cancer recurrence emphasise fat reduction and increased vegetable intake (Pierce et al, 1997;Wynder et al, 1997).…”
Section: Introductionmentioning
confidence: 99%